Flow and Heat Transfer Characteristics in Micro and Mini Communicating Pressure Driven Channel Flows by Numerical Simulations - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
The flow and heat transfer characteristics are investigated in micro and mini communicating channel pressure driven flows by 2D numerical simulations using a computational method. The continuum based Navier-Stokes and continuity equations are solved by the Spectral Element Method (SEM). Flow and heat transfer characteristics are determined for 10 < Re < 227. The 2D communicating channel physical domain contains many blocks within the parallel,.upper and lower walls. A periodic computational domain of length 2 (L) over cap and an aspect ratio of r = (a) over cap/(2 (L) over cap) is used, where a is the height of block within the channel and (L) over cap is the periodic length. For low Reynolds number, viscous forces dominate and two stationary symmetric vortices are generated between blocks with very laminar parallel viscous flow in the upper and lower communicating channel. For moderate Reynolds numbers, numerical results show a transition scenario with two Hopf flow bifurcations, as the flow evolves from a laminar to a time-dependent flow regime. The first Hopf bifurcation B-1 occurs at a critical Reynolds number (Re-c1) leading to a periodic flow characterized by a frequency omega(1). A quasi periodic flow sets in for higher Reynolds numbers through a second Hopf flow bifurcation B-2 occurring at a critical Reynolds number (Re-c2 < Re-c1) with two frequencies omega(1) and omega(2), and a linear combinations of omega(1) and omega(2). The existence of either regime will depend on the previous flow regime, the process of furthering the Reynolds number from one condition to another, and the aspect ratio r. Numerical results show that Nusselt numbers are at least 50% larger in quasi periodic than in periodic and laminar flow regimes. The existence of periodic and quasi periodic flows leads to a heat transfer enhancement at the same Reynolds number. (C) 2012 Elsevier Ltd. All rights reserved.